The storage of water in sand : an investigation of the properties of natural and artificial sand reservoirs and of methods of developing such reservoirs - Wipplinger, O. (Otto) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Sc.)--Stellenbosch University, 1953.